EXTH-64. SMALL GTPASES IN MENINGIOMAS: PROLIFERATION, MIGRATION, SURVIVAL, POTENTIAL TREATMENT AND INTERACTIONS. (9th November 2020) - Kesseler, Christoph; Kahr, Julian; Waldt, Natalie; Stroscher, Nele; Liebig, Josephine; Angenstein, Frank; Kirches, Elmar; Mawrin, Christian
Abstract: PURPOSE: To evaluate the role of the small GTPases RhoA, Rac1 and Cdc42 in meningiomas as therapeutic targets and their interactions in meningiomas. EXPERIMENTAL DESIGN: We analyzed expression of GTPases in human meningioma samples and meningioma cell lines of various WHO grades. Malignant IOMM-Lee meningioma cells were used to generate shRNA mediated knockdowns of GTPases RhoA, Rac1 or Cdc42 and to study knockdown effects on proliferation and migration, as well as analysis of cell morphology by confocal microscopy. The same tests were used to investigate effects of the two inhibitors Fasudil and EHT-1864 of malignant IOMM-Lee, KT21 and benign Ben-Men cells and the effects of these drugs on IOMM-Lee knockdown cells. The effects of GTPase knockdowns and Fasudil treatment were studied in terms of overall survival by intracranial xenografts of mice. Potential interactions of GTPases regarding NF2, mTOR and FAK-Paxillin were examined. RESULTS: Small GTPases were upregulated in meningiomas of higher tumor grades. Reduced proliferation and migration could be achieved by GTPase knockdown in IOMM-Lee cells. Additionally, the ROCK-inhibitor Fasudil and Rac1-inhibitor EHT-1864 reduced proliferation in different meningioma cell lines and reduced proliferation and migration independent of GTPase knockdowns/status. Moreover, overall survival in vivo could also be increased by knockdowns of RhoA and Rac1 as well as Fasudil treatment. GTPase expression was affected dependent on the NF2 status but effects were not very distinct, indicating that NF2 is not strongly involved in GTPase regulation in meningiomas. In terms of mTOR and FAK-Paxillin signaling, each GTPase changes those pathways in a different manner. CONCLUSION: Small GTPases are important effectors in meningioma proliferation and migration in vitro as well as survival in vivo and their inhibition should be considered as potential treatment option.